2011
DOI: 10.7589/0090-3558-47.1.126
|View full text |Cite
|
Sign up to set email alerts
|

Ecology and Dynamics of the Blood Parasite, Hepatozoon Tuatarae (Apicomplexa), in Tuatara (Sphenodon Punctatus) on Stephens Island, New Zealand

Abstract: ABSTRACT:We explored infection patterns and temporal dynamics of the protozoan blood parasite Hepatozoon tuatarae (Apicomplexa) infecting the tuatara (Sphenodon punctatus), a protected reptile living on Stephens Island, New Zealand. In March 2006, we surveyed tuatara in five study sites to examine spatial variation in infection prevalence, and four times, from May 2005 to November 2006, we recaptured marked individuals within three study sites to examine the temporal dynamics of infection. We also examined how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 52 publications
(70 reference statements)
2
15
1
Order By: Relevance
“…For example, in the spiny‐tailed iguana ( Ctenosaura melansterna ), whose lifespan is estimated around 20 years, prevalence and parasitemias of blood parasites declined with increasing host age (Davis et al., ). A similar result was found regarding blood parasites in the tuatara, which have life spans of over 50 years (Godfrey, Nelson, & Bull, ).…”
Section: Discussionsupporting
confidence: 80%
“…For example, in the spiny‐tailed iguana ( Ctenosaura melansterna ), whose lifespan is estimated around 20 years, prevalence and parasitemias of blood parasites declined with increasing host age (Davis et al., ). A similar result was found regarding blood parasites in the tuatara, which have life spans of over 50 years (Godfrey, Nelson, & Bull, ).…”
Section: Discussionsupporting
confidence: 80%
“…However, this pattern is not linear among hemogregarine infections, especially when considering long-lived reptile species. Studies conducted on snakes [35], [36], [95] and tuataras [96] have found an inverse association to that reported here, with larger individuals having lower intensities. These contrasting infestation patterns may be related to differences in the pathogenesis of hemogregarine infections between short- and long-lived reptiles.…”
Section: Discussionsupporting
confidence: 66%
“…Furthermore, a literature review on the subject of age-related effects on blood parasites in lizards (including genus Lacerta , Sceloporus , and Tiliqua ) indicated that higher prevalence in adults is the dominant pattern [ 26 ]. A recent exception to this was a study of parasites in tuatara ( Sphenodon punctatus ), which, like our investigation, found infections with Hepatozoon tuatarae decreased in frequency and severity with host size [ 27 ]. The reasons for these variable findings are unknown but could be related to the biology of the hosts, including overall size and longevity.…”
Section: Discussioncontrasting
confidence: 70%